Psychological suspense in the plot of Mcmahon's The Children on the Hill - Syuhra, Marsha Aqillah Putri; Sufi Ikrima Sa’adah (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2024)
Complex plots filled with surprises are often found in literary works of psychological suspense, where, in the end, the reader’s perspective will be completely twisted. This research aims to elaborate on the feature of psychological suspense in Jennifer McMahon’s work, The Children on the Hill. This novel tells how Violet and Lizzy dig for information to find the truth about something in each different time zone. It is none other than the dark family secret and the truth about the real monster. The descriptive qualitative method is applied to explain the plot of The Children on the Hill in detail and thoroughly. Through the application of Wyatt and Saricks’ theory of genre fiction characteristics, several plots that give the effect of psychological suspense were identified. The story was complex in that the truth of the matter was jumbled as information overlapped. Another surprising element is where the incident depicts a mental state that seems to be trapped in a nightmare and feels like it is beyond rationale. Both characters have their own complicated and heart-breaking problems as they go deeper to discover the truth. These plots show compatibility with Wyatt and Saricks’ theory of psychological suspense.